The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1038/nsmb.1818
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii calcium-dependent protein kinase 1 is a target for selective kinase inhibitors

Abstract: New drugs are needed to treat toxoplasmosis. Toxoplasma gondii calcium-dependent protein kinases (TgCDPKs) are attractive targets because they are absent in mammals. We show that TgCDPK1 is inhibited by low nanomolar levels of bumped kinase inhibitors (BKIs), compounds designed to be inactive against mammalian kinases. Cocrystal structures of TgCDPK1 with BKIs confirm that the structural basis for selectivity is due to the unique glycine gatekeeper residue in the ATP-binding site at residue 128. We show that B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
260
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(269 citation statements)
references
References 51 publications
6
260
3
Order By: Relevance
“…Tachyzoites of N. caninum isolates Nc-Liverpool (Nc-Liv) and Nc-Spain7, T. gondii strains ME49 and RH, the T. gondii strain CDPK1_G128M overexpressing a CDPK1 with the gatekeeper mutation G128M, and an isogenic strain, T. gondii CDPK_wt, expressing the wildtype CDPK1 (12) were all maintained by serial passages in either Vero cells or HFF in their respective media (14,15). Tachyzoites were harvested by removing infected cell layers with a rubber cell scraper followed by repeated passages through a 25-gauge needle at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tachyzoites of N. caninum isolates Nc-Liverpool (Nc-Liv) and Nc-Spain7, T. gondii strains ME49 and RH, the T. gondii strain CDPK1_G128M overexpressing a CDPK1 with the gatekeeper mutation G128M, and an isogenic strain, T. gondii CDPK_wt, expressing the wildtype CDPK1 (12) were all maintained by serial passages in either Vero cells or HFF in their respective media (14,15). Tachyzoites were harvested by removing infected cell layers with a rubber cell scraper followed by repeated passages through a 25-gauge needle at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…In many apicomplexan CDPK1 enzymes, including T. gondii and N. caninum, the ATP binding pocket is characterized by a glycine as the smallest possible gatekeeper residue. The T. gondii strain CDPK1_G128M, overexpressing a CDPK1 version with a muta-tion (G to M) in the ATP binding pocket, was found to be much less sensitive to BKIs (12).…”
mentioning
confidence: 99%
“…A Tet-inducible knockout of TgCDPK1 blocks the secretion of micronemes, which results in impaired gliding motility, invasion, and egress (Lourido et al, 2010). Several specific inhibitors were designed against TgCDPK1, including pyrazolopyrimidine derivatives for which a gatekeeper mutant was shown to restore microneme secretion in the presence of the drug (Johnson et al, 2012;Kieschnick et al, 2001;Ojo et al, 2010;Sugi et al, 2010).…”
Section: Microneme Secretion and Egressmentioning
confidence: 99%
“…The in vitro susceptibility of TgCDPK1 to 1NM-PP1 (IC 50 =0.02 μM) [8] was not very different from that of susceptible mutated mouse CaMKII (IC 50 =0.03 μM) [15]. TgCDPK1 was reported to localize in the parasite cytosol and not to be secreted [9].…”
mentioning
confidence: 93%
“…Using in silico prediction, we found that T. gondii calcium-dependent protein kinase 1 (TgCDPK1), which has a glycine residue at the gate site of the ATP binding pocket, was the main T. gondii analog-sensitive kinase [12]. In silico prediction, an in vitro culture assay using transgenic parasites, and a structural analysis of TgCDPK1 all showed that TgCDPK1 is a target of BKI [6,8,12]. TgCDPK1 is involved in parasite attachment, invasion, egress, and secretion in vitro [5,6].…”
mentioning
confidence: 99%